PLURALITY EXIBITITION AND ITS IMPLICATION TO BUILD TOLERANCE ISLAMIC COLLEGE (A CASE STUDY AT PONDOK PESANTREN TEBUIRENG, JOMBANG) - Mursyid , Atmari (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
This article is half of my last research ideas, on our long term anexiety of Pesantren and Tolerance Values. This research arose from several facts which indicated that Islamic College had deep cultural values to accept social plurality as their system of beliefs. Even if, not all Islamic Colleges could implement them. This article, specially, will discribe what PP. Tebuireng, Jombang, implemented to make their students, become tolerance people. Based on their five pillars, foundations or Islamic Colleges identity. The article also will introduce what the writer call as ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œTolerance ExhibitionÃƒÂ¢Ã¢â€šÂ¬Ã‚Â, which is only be one of specific identity in its teritory. Like a scientific writing, phenomenological and rational choices theory are become theoritical framework to explain how this founding can be implemented generally in each Islamic College. In the end, this paper will conclude that PP. Tebuireng may become a role model to implement tolerance education, even institutionally or practically by its teachers and stakeholders.